Successful treatment with carfilzomib and dexamethasone for relapsed/refractory POEMS syndrome: a case report and review of literature - Yu, Shuang; Li, Xiangxin; Peng, Jun; Wang, Luqun; Li, Hao (Frontiers in Oncology, 2025)
BackgroundPOEMS syndrome is a rare multisystem disease secondary to plasma cell neoplasm. Due to its rarity, there are no internationally agreed treatment standards, with very limited data to guide management in the relapse setting.Case presentationWe describe a 51-year-old woman with initially presented with fatigue, anorexia, nausea, abdominal distension, and edema of the face and both lower limbs, who was diagnosed with POEMS syndrome accompanied with Raynaud’s phenomenon and cardiac involvement. After multiple lines of treatment, including bortezomib, cyclophosphamide, and dexamethasone (VCD), ixazomib, and daratumumab along with dexamethasone (DD), her clinical and laboratory features, and cardiovascular system continued to deteriorate. Then we started carfilzomib and dexamethasone, and the patient achieved a complete response. She did not develop significant cardiac toxicity and peripheral neuropathy. A total of 4 cycles of carfilzomib and dexamethasone were administered monthly, followed by autologous stem cell transplantation (ASCT). After 4 months of follow-up, a complete remission persists, and no significant complications were observed.ConclusionWe report on the first case of relapsed/refractory POEMS syndrome who received carfilzomib and dexamethasone, and achieved very good remission. Carfilzomib may be a safe and effective treatment option for patients with relapsed/refractory POEMS syndrome.